Mutational signature and clonal relatedness of recurrent urothelial carcinomas with aristolochic acid - Zhu, Jie; Ai, Qing; Cheng, Qiang; Shen, Dan; Dong, Zhouhuan; Li, Jie; Shen, Donglai; Wang, Wei; Zhang, Xu; Li, Hongzhao (Frontiers in Oncology, 2022)
Urothelial carcinomas (UCs) are malignant tumors that arise from the lower and upper urinary tract and are characterized by multiple recurrences. Aristolochic acid (AA) is a potent nephrotoxin and human carcinogen associated with UC. East Asian populations with a high UC prevalence have an unusual genome-wide AA-induced mutational pattern. To address the genomic differences and clonal relatedness between primary and recurrent tumors in the UCs with AA pattern, we investigated the genomic differences and tumor microenvironment (TME) of AA and non-AA UCs. 17 UC patients were recruited, with nine documented AA exposure. Eleven of them showed recurrence. After-surgery tissues of primary and paired recurrent tumors were collected. Capture-based targeted deep sequencing was performed using a commercial panel consisting of 520 cancer-related genes. Tumor-infiltrating lymphocytes (TILs) were identified with an immunofluorescence-based microenvironment analysis panel (MAP). Hierarchical clustering based on the COSMIC signatures confirmed two significant subtypes: AA Sig and non-AA Sig. AA Sig was associated with AA-containing herbal drug intake, recurrence, and higher tumor mutation burden (TMB). The clonal architecture of UCs revealed three types of clonal evolution patterns. Non-AA Sig cohort showed shared clonal origin of primary and recurrent tumors. AA Sig showed heterogeneity and had multiple independent origins. Recurrent tumors as second primary tumors in AA Sig showed immunoreactive TME, indicating a better response with immune checkpoint inhibitor therapy. The AA mutational signature and unique immune profiles are helpful molecular markers to distinguish AA exposure from other carcinogens. These results also provide new insights into the origin of recurrent UCs that could affect treatment strategies.